How effective is collaborative reflective practice in enabling cognitive transformation in English language teachers?. Issue 4 (4th July 2018) - Godínez Martínez, Jovanna Matilde
ABSTRACT: This paper reports on an action research study conducted in 2015 with five in-service English language teachers from an ELT undergraduate programme of a university in the central part of Mexico over a period of 9 weeks by means of two video recorded classroom observations and different spaces for professional dialogue (a focus group, one on one feedback discussions and personal interviews). Overall, the study revealed that teachers have the ability to be critically reflective about their teaching given the appropriate conditions which Reflective Practice (RP) necessitates such as opportunity, time, and assistance from others, often lacking in everyday teaching scenarios, traditional evaluative classroom observations and conventional teacher education programmes. Hence, by challenging the 'status quo' of classroom observations in this context, the RP processes carried out helped teachers understand and reconstruct their teaching knowledge especially in terms of students' responses to their instructional decisions and the impact this had on how their classes unfolded. It promoted an alternative way to fulfil the goal of teacher development, not through a 'transmission' model of education but through a process in which teachers learn and continue to develop their skill in dialogue within a professional community.